Inverse MCRT Method for Obtaining Solar Concentrators with Quasi-Planar Flux Distribution. (May 2015) - Serrano-Aguilera, J.J.; Valenzuela, L.; Fernández-Reche, J.
Abstract: A numerical algorithm has been developed in order to get reflectors geometry so that the desired flux distribution is approximately obtained. This new method opens up the opportunity to design ad-hoc line-focus solar reflectors for a specific purpose from the required concentrated flux distribution. A new design for PTC reflectors is proposed, getting a quasi-planar distribution around the absorber. This algorithm can also be applied not only to round absorbers in PTC applications but others like flat absorbers useful for concentrated solar photovoltaic/thermal systems. The proposed new reflector geometries will be compared to the classical Eurotrough-type parabolic-trough geometry by means of the intercept factor and the tolerance to absorber displacements respect to the design location.